Do Family Caps Reduce Out-of-Wedlock Births? Evidence from Arkansas, Georgia, Indiana, New Jersey and Virginia - Wendy Tanisha Dyer; Robert W. Fairlie (Yale University, Economic Growth Center, 2003)
Using Current Population Survey (CPS) data from 1989 to 1999, we examine the impact of family cap policies, which deny incremental welfare benefits, on out-of-wedlock birth rates. We use the first five states that were granted waivers from the Department of Health and Human Services to implement family caps as 'natural experiments.' Specifically, we compare trends in out-of-wedlock birth rates in Arkansas, Georgia, Indiana, New Jersey and Virginia to trends in states that did not implement family caps or any other waivers prior to the Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA). We employ several techniques to increase the credibility of results from our 'natural experiment,' such as the inclusion of multiple comparison groups, controls for differential time trends, and 'difference-in-difference-indifferences' estimators. Our regression estimates generally do not provide evidence that family cap policies reduce the incidence of out-of-wedlock births among single, less-educated women with children.
Keywords: I3; J1; 330; Welfare; Family Caps; Fertility; Nichteheliche Kinder; Familienleistungsausgleich; Arkansas; Georgia (Staat); Indiana; New Jersey; Virginia